Centro de información turística y la orientación del visitante en el cantón Montalvo - Pazmiño Figueroa, Erika Paola (2019)
The present investigation is focused on integrating the participation of the authorities together with the population through strategies, in order to build a tourist information center to guide the visitor who arrives in Canton Montalvo, in order to transmit the most complete information about of the different natural, historical and cultural resources of the area, as well as the offer of restaurants and accommodation and at the same time take advantage of in a rational way the natural resources that the canton possesses to improve local tourism development. Through the development of the research, different techniques were used to collect the information, the interview and survey methods were also used, which were carried out to the authorities and tourists, and as a result it was determined that it is important to build an information center tourist for the orientation of the visitor in the Canton